Chemical and physical properties of carbonated HA affect breast cancer cell behavior - Choi, Siyoung (Acta Biomater, 2015)
Breast microcalcifications are routinely explored for mammographic detection of breast cancer and primarily composed of non-stoichiometric hydroxyapatite (Ca(10-x)(PO(4))(6-x)(CO(3))(x)(OH)(2-x)) (HA). Interestingly, HA morphology and carbonate substitution vary in malignant vs. benign lesions. However, whether or not these changes (i) are functionally linked and (ii) impact malignancy remains unclear due in part to a lack of model systems that permit evaluating these possibilities. Here, we have adapted a 96 well-based mineralized culture platform to investigate breast cancer cell behavior in response to systematic changes in the chemical and physical properties of HA. By adjusting the carbonate content of the simulated body fluid (SBF) solutions used during growth, we can control the morphology and carbonate substitution of the deposited HA. Our results suggest that both the combined and individual effects of these differences alter breast cancer cell growth and secretion of tumorigenic interleukin-8 (IL-8). Consequently, changes in both HA carbonate incorporation and morphology impact the behavior of breast cancer cells. Collectively, our data underline the importance of biomineralized culture platforms to evaluate the functional contribution of HA materials properties to the pathogenesis of breast cancer.